Endomicroscopic optical coherence tomography for cellular resolution imaging of gastrointestinal tracts. Issue 4 (20th November 2017) - Luo, Yuemei; Cui, Dongyao; Yu, Xiaojun; Bo, En; Wang, Xianghong; Wang, Nanshuo; Braganza, Cilwyn S.; Chen, Shufen; Liu, Xinyu; Xiong, Qiaozhou; Chen, Si; Chen, Shi; et al.
Abstract : Our ability to detect neoplastic changes in gastrointestinal (GI) tracts is limited by the lack of an endomicroscopic imaging tool that provides cellular‐level structural details of GI mucosa over a large tissue area. In this article, we report a fiber‐optic‐based micro‐optical coherence tomography (μOCT) system and demonstrate its capability to acquire cellular‐level details of GI tissue through circumferential scanning. The system achieves an axial resolution of 2.48 μm in air and a transverse resolution of 4.8 μm with a depth‐of‐focus (DOF) of ~150 μm. To mitigate the issue of limited DOF, we used a rigid sheath to maintain a circular lumen and center the distal‐end optics. The sensitivity is tested to be 98.8 dB with an illumination power of 15.6 mW on the sample. With fresh swine colon tissues imaged ex vivo, detailed structures such as crypt lumens and goblet cells can be clearly resolved, demonstrating that this fiber‐optic μOCT system is capable of visualizing cellular‐level morphological features. We also demonstrate that time‐lapsed frame averaging and imaging speckle reduction are essential for clearly visualizing cellular‐level details. Further development of a clinically viable μOCT endomicroscope is likely to improve the diagnostic outcome of GI cancers. Abstract : This article presents a micro‐optical coherence tomography (μOCT) endomicroscopy system capable of acquiring cellular‐level details of gastrointestinal (GI) tissues through circumferential scanning with 2.48‐μm axial resolution and 4.8‐μm transverse resolution along the depth‐of‐focus of ~150 μm. The imaging results demonstrate the feasibility of this fiber‐optic μOCT system for visualizing cellular‐level morphological features, which paves the way for the surveillance, detection and treatment of GI tract diseases.